1998
DOI: 10.1029/97ja02986
|View full text |Cite
|
Sign up to set email alerts
|

The driving of the plasma sheet by the solar wind

Abstract: Abstract. The coupling of the plasma sheet to the solar wind is studied statistically using measurements from various satellite pairs: one satellite in the solar wind and one in either the magnetotail central plasma sheet or the near-Earth plasma sheet. It is found that the properties of the plasma sheet are highly correlated with the properties of the solar wind: specifically that (1) the density of the plasma sheet is strongly correlated with the density of the solar wind, (2) the temperature of the plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
394
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(432 citation statements)
references
References 126 publications
36
394
2
Order By: Relevance
“…From 3 two-satellite studies that the authors have performed involving simultaneous solar wind and plasma sheet data (ISEE-3 and ISEE 2, IMP-8 and 1989-046, and WIND and 1994-085), it has been found that the plasma sheet density is strongly correlated with the solar wind density and that the plasma sheet temperature is strongly correlated with the solar wind flow speed [Delapp et al, 1995;Borovsky et al, 1997bBorovsky et al, , 1998a. (Whereas the plasma sheet density is poorly correlated with the solar wind speed and the plasma sheet temperature is poorly correlated with the solar wind density.)…”
Section: Goertz and Baumjohann [1991] Predicted This Decreasementioning
confidence: 99%
“…From 3 two-satellite studies that the authors have performed involving simultaneous solar wind and plasma sheet data (ISEE-3 and ISEE 2, IMP-8 and 1989-046, and WIND and 1994-085), it has been found that the plasma sheet density is strongly correlated with the solar wind density and that the plasma sheet temperature is strongly correlated with the solar wind flow speed [Delapp et al, 1995;Borovsky et al, 1997bBorovsky et al, , 1998a. (Whereas the plasma sheet density is poorly correlated with the solar wind speed and the plasma sheet temperature is poorly correlated with the solar wind density.)…”
Section: Goertz and Baumjohann [1991] Predicted This Decreasementioning
confidence: 99%
“…The energy stored for the triggering of the X lines and the substorm in the tail under northward IMF is just the remnant energy in the period of preexiting southward IMF [Li et al, 2008;Du et al, 2011;Miyashita et al, 2011]. Due to the weaker convection electric field for northward than southward IMF [Maezawa, 1976;Usadi et al, 1993;Borovsky et al, 1998;Petrukovich et al, 2003;Wang et al, 2006], it is prone to conjecture that not enough energy and/or magnetic flux can be deposited in the tail to form a thin current sheet and generate an X line under northward IMF condition [Min et al, 1985;Ma et al, 1995;Pritchett and Coroniti, 1994;Petrukovich et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive statistical studies of the plasma within the near-Earth magnetosphere have previously revealed the behaviour of such parameters (e.g. Baumjohann et al, 1988;Newell and Meng, 1992;Borovsky et al, 1998;Wing and Newell, 1998;Měrka et al, 2002;Tysganenko and Mukai, 2003;Wing et al, 2005;Neagu et al, 2005;Denton et al, 2005Denton et al, , 2006Borovsky and Denton, 2006a, b;Lavraud et al, 2005Lavraud et al, , 2006Thomsen et al, 2007;Nagata et al, 2007;Åsnes et al, 2008) under a variety of conditions. The primary aim of the work outlined in the current paper is to reveal the averaged bulk parameters in the magnetosphere as a first step to a determination of how such parameters evolve during geomagnetic disturbances.…”
Section: Introductionmentioning
confidence: 99%